Exploring employee motivation in Polish family firms. Case of retail sector - Kubica, Iwona; Szarucki, Marek (Business, Management and Economics Engineering, 2016)
This article focuses on the construct employee motivation in family businesses. Its main aim is to examine employee motivation in family firms on the example of selected companies from the retail sector in Poland. First, selected theoretical aspects of family business functioning have been discussed. Second, the special character of employee motivation in family firms has been presented, in the light of literature. As methods of research literature review and a semistructured questionnaire were applied. The empirical part presents the results of the analysis of the employee motivation in the selected firms. Finally, some insights and recommendations for future research were proposed.